Ocular morbidities in pediatric outpatient population at a tertiary care ophthalmic centre: a descriptive study - Gupta, Prabha; Gupta, Vijay (International Journal of Contemporary Pediatrics, 2018)
Background: Ocular problems in children are unique and different from adults, because of their inability to express their problems and potential to develop amblyopia. Screening at the level of schools cover school age going children only while congenital and infantile disorder can cause significant morbidity if remain untreated . Hence the present study was conducted to determine the pattern of Ocular morbidities in children uptil 15 years of age. Methods: It is a hospital based retrospective study. Outpatient department (OPD) records of all new patients aged 15 years and younger were reviewed. The age at presentation, sex and clinical diagnosis were recorded from OPD records. Data was recorded and analyzed. Results: Total of 480 children was enrolled with ocular problems. Majority belong to 11-15 years of age group. Conjunctival morbidity was most commonly encountered in 146 (30.41%) children followed by refractive error 82 (17.07%) and lid problems in 81 (16.87%) patients. Ocular trauma constitutes 54 (11.25%) children of the total. Conclusions: In view of high prevalence of Conjunctival and refractory errors in pediatrics population, there is a need of health counseling of parents regarding ocular hygiene, protection and regular refraction of children to identify the ocular morbidity at the earliest and prevent the long term complications.